(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In this article the problems of borrowing are probed in the modern Ukrainian terminology vocabulary. The role of anglicizms is determined in modern Ukrainian economic terminology. The processes of included in the language of foreign vocabulary and feature of its use are examined.